Current status of KRAS G12C inhibitors in NSCLC and the potential for combination with anti-PD-(L)1 therapy: a systematic review - Zhang, Fan; Wang, Banglu; Wu, Menghuan; Zhang, Liwen; Ji, Mei (Frontiers in Immunology, 2025)
In recent years, precision medicine for non-small cell lung cancer (NSCLC) has made significant strides, particularly with advancements in diagnostic and therapeutic technologies. Targeted 7therapies and Anti-PD-(L)1 Therapies have emerged as vital treatment options, yet KRAS mutations, especially KRAS G12C, have been historically difficult to address. Due to the unique activation mechanism of KRAS G12C has led to the development of specific inhibitors, such as AMG 510 and MRTX849, which show promising therapeutic potential. However, results from the CodeBreaK 200 Phase III trial indicated that AMG 510 did not significantly improve overall survival compared to docetaxel. Resistance after prolonged use of KRAS G12C inhibitors continues to pose a challenge, prompting interest in new drugs and combination strategies. KRAS mutations can impair tumor-infiltrating T cell function and create an immunosuppressive tumor microenvironment, making the combination of KRAS G12C inhibitors with anti-PD-(L)1 therapies particularly appealing. Preliminary data suggest these combinations may enhance both survival and quality of life, though safety concerns remain a barrier. Ongoing research is crucial to refine treatment regimens and identify suitable patient populations. This review focuses on the development of KRAS G12C inhibitors in monotherapy and combination therapies for NSCLC, discussing major clinical trials and future research directions.